2021
DOI: 10.1002/slct.202101752
|View full text |Cite
|
Sign up to set email alerts
|

Wacker‐Tsuji‐Type Oxidation Reactions of Styrene Derivatives Catalyzed by Ferrate

Abstract: We have developed a Wacker-Tsuji-Type oxidation reaction of styrene derivatives catalyzed by a bench-stable ferrate. This oxidation reaction, which uses molecular oxygen as the sole oxidant and 1,1,3,3-tetramethyldisiloxane (TMDS) as a reductant, can realize the oxidation of styrene derivatives to ketones in good yield. In addition, this ferrate-based system can achieve the cleavage of the CÀ C double bond of α-phenyl-substituted styrene derivatives, providing the one-carbon-degraded ketones in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Similarly, Yamaguchi and co‐workers developed an iron‐catalyzed Wacker‐type oxidation of styrenes to ketones by utilizing 5 mol % of a ferrate Fe III complex as precatalyst (Scheme 14). [31] The reaction conditions are similar to those reported independently by the groups of Han and Knölker. They consist of TMDS (TMDS=1,1,3,3‐tetramethyldisiloxane) as the reducing agent in ethanol at 80 °C in an O 2 atmosphere.…”
Section: Iron‐based Catalysts For Wacker‐type Reactionssupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, Yamaguchi and co‐workers developed an iron‐catalyzed Wacker‐type oxidation of styrenes to ketones by utilizing 5 mol % of a ferrate Fe III complex as precatalyst (Scheme 14). [31] The reaction conditions are similar to those reported independently by the groups of Han and Knölker. They consist of TMDS (TMDS=1,1,3,3‐tetramethyldisiloxane) as the reducing agent in ethanol at 80 °C in an O 2 atmosphere.…”
Section: Iron‐based Catalysts For Wacker‐type Reactionssupporting
confidence: 80%
“…Similarly, Yamaguchi and co-workers developed an ironcatalyzed Wacker-type oxidation of styrenes to ketones by utilizing 5 mol % of a ferrate Fe III complex as precatalyst (Scheme 14). [31] The reaction conditions are similar to those Scheme 10. Postulated reaction mechanism for the Wacker-type oxidation of terminal olefins to ketones catalyzed by a hexadecafluorinated iron(II) phthalocyanine (the phthalocyanine ligand around the iron center is not depicted for the sake of clarity).…”
Section: Iron-based Catalysts With Markovnikov Selectivitymentioning
confidence: 99%
“…A similar strategy was also developed by Yamaguchi and co-workers for an air-and moisture-stable bis(triphenylphosphoranylidene)ammonium ferrate (PPN)[FeCl 4 ]-catalyzed Wacker-type oxidation of styrenes to ketones by utilizing molecular oxygen as the sole oxidant. 26 Scheme 6 Iron-catalyzed Wacker-oxidation under air at room temperature Y. Gao et al…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, many catalysts, especially Brønsted acids or Lewis acids, have been developed for the synthesis of β-alkoxy alcohols. [5][6][7][8][9] As a part of our ongoing project on transformations of organic molecules using organosilicon compounds, [10] we found that commercially available Ph 3 SiH works as a Lewis-acidic catalyst for the ring-opening reactions of di-and tri-substituted epoxides with alcohols. Herein, we report a simple method for the synthesis of β-alkoxy alcohols via the ring-opening reaction of di-and tri-substituted epoxides by alcohols using inexpensive and benign Ph 3 SiH as a catalyst under nearly neutral reaction conditions (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%